Application of Four-Hands Piano Virtual Learning Videos for Learning to Read Basic Level Block Notation - Nadine Rizkita; Yudi Sukmayadi (Universitas Negeri Medan, 2022)
Learning media can be said as a tool in the learning process, with everything that can be used to stimulate the thoughts, feelings, attention and abilities or skills of students so that it can encourage the learning process. The material presented must be systematically and psychologically designed in order to prepare effective instruction. This article discusses learning to read piano instrument block notes using a virtual four-handed piano learning video that can be easily accessed and studied individually. However, the success of the four-handed virtual piano learning video in learning piano block notation has various aspects that must be considered so that the music-making features available in the video can be used effectively. This article aims to discuss the level of student satisfaction in the use of four hands virtual piano learning videos, identify obstacles in learning, provide feedback and important information for learning improvement. This research uses descriptive analysis method. Involving three course students who already understand reading block notation, in the Borg and Gall method, this product testing is in stage 1, where the subjects involved are still in small scope. The results of this test show some of the advantages and disadvantages of learning videos, both in terms of audio, visual, material, material delivery techniques, to the level of students' understanding of the material.